Biopolymer Skeleton Produced by Rhizobium radiobacter: Stoichiometric Alternation of Glycosidic and Amidic Bonds in the Lipopolysaccharide O‐Antigen. (10th March 2020) - Speciale, Immacolata; Di Lorenzo, Flaviana; Gargiulo, Valentina; Erbs, Gitte; Newman, Mari‐Anne; Molinaro, Antonio; De Castro, Cristina
Abstract: The lipopolysaccharide (LPS) O‐antigen structure of the plant pathogen Rhizobium radiobacter strain TT9 and its possible role in a plant‐microbe interaction was investigated. The analyses disclosed the presence of two O‐antigens, named Poly1 and Poly2. The repetitive unit of Poly2 constitutes a 4‐α‐l ‐rhamnose linked to a 3‐α‐d ‐fucose residue. Surprisingly, Poly1 turned out to be a novel type of biopolymer in which the repeating unit is formed by a monosaccharide and an amino‐acid derivative, so that the polymer has alternating glycosidic and amidic bonds joining the two units: 4‐amino‐4‐deoxy‐3‐O‐methyl‐d ‐fucose and (2′R, 3′R, 4′S)‐ N ‐methyl‐3′, 4′‐dihydroxy‐3′‐methyl‐5′‐oxoproline). Differently from the O‐antigens of LPSs from other pathogenic Gram‐negative bacteria, these two O‐antigens do not activate the oxidative burst, an early innate immune response in the model plant Arabidopsis thaliana, explaining at least in part the ability of this R. radiobacter strain to avoid host defenses during a plant infection process. Abstract : Die Hülle des Rhizobium‐radiobacter ‐Stammes TT9 wird mithilfe einer Lipopolysaccharid‐Mischung identifiziert, die zwei O‐Antigene, Poly1 und Poly2, präsentiert, die nicht in der Lage sind, das Abwehrsystem in der Modellpflanze Arabidopsis thaliana auszulösen. Die Poly2 ‐Wiederholungseinheit besteht aus Rhamnose und Fucose, während Poly1 eine neuartige Polymerarchitektur aufweist, die abwechselnd aus einem Monosaccharid und einem Aminosäurederivat besteht.